Assessment of Intracranial Collateral Circulation Using Novel TCCS Grading System in Patients With Symptomatic Carotid Occlusion - Abd-Allah, Foad; Rizk, Haytham; Farrag, Mohammad Ahmed; Shaaban, Mohamed Hafez; Nasreldein, Ahmed (Frontiers in Neurology, 2020)
Abstract Objectives: To establish a novel Transcranial color coded sonography (TCCS) grading system for collateral circulation in cases of symptomatic chronic total carotid occlusion (TCO), and to correlate this new grading system with cerebrovascular reserve capacity (CVR) measured by SPECT. Methods: Thirty four patients with symptomatic chronic TCO recruited from the neurovascular ultrasound laboratory of the department of Neurology at Cairo University Hospital during 3 years’ time period and diagnosed by color-coded duplex were subjected to: clinical assessment, grading of cerebral collaterals using a proposed TCCS criteria, Brain SPECT studies at rest and with dipyridamole stress. Results: The new grading system for cerebral collateral circulation showed a significant positive correlation with CVR (P value < 0.001 and Spearman correlation coefficient 0.686) Conclusion: The current study showed that this new TCCS grading system for cerebral collaterals is a reliable indicator for cerebral perfusion and reserve capacity in cases of chronic symptomatic TCO. .